Comparación de comisiones por flujo y por saldo en sistemas de pensiones con cuentas individuales de capitalización - Chávez-Bedoya, Luis (2016)
In this present article, we develop a discrete-time methodology to comparefront-end load and balance fees in the accumulation phase of a definedcontributionpension fund under a system of individual accounts. Using thismethodology, we study the effect of risk aversion and other relevant variables inthe performance and suitability of the aforementioned types of fees. Finally, wecarry out a practical application and show the results for the Peruvian PrivatePension System, including indifference values between fees and certaintyequivalent ratios.